The Traditional Chinese Medicine Fuyou Formula Alleviates Precocious Puberty by Inhibiting GPR54/GnRH in the Hypothalamus - Bai, Guo-liang; Hu, Kai-li; Huan, Yi; Wang, Xing; Lei, Lei; Zhang, Meng; Guo, Chun-yan; Chang, Hong-sheng; Zhao, Li-bo; Liu, Jing; Shen, Zhu-fang; Wang, Xiao-ling; et al. (Frontiers in Pharmacology, 2021)
The purpose of this study was to explore the effect of the traditional Chinese medicine (TCM) Fuyou (Fy) formula on precocious puberty (PP). The Fy formula may exert an effect in female rats with PP and GT-7 cells through the GPR54/GnRH signaling pathway. To confirm the effect of the Fy formula on PP through the GPR54/GnRH signaling pathway, we first treated GT1-7 cells with the Fy formula and observed changes in the expression of related genes and proteins and in GnRH secretion. Then, we randomly divided young female Sprague-Dawley (SD) rats into the control group, model group, leuprorelin group and the Fy formula group. A PP model was established by injection of danazol on postnatal day (PND) 5, and the Fy formula was administered on PND15. The time of vaginal opening, the wet weights of the ovary and uterus, serum hormone levels and the expression of hypothalamic-related genes were observed. We found that the Fy formula delayed vaginal opening, decreased the wet weights and coefficients of the ovary and uterus, decreased the levels of serum hormones (E2, FSH and LH) and the cellular GnRH level, and downregulated the gene expression of Kiss1, GPR54 and GnRH in the hypothalamus and the gene and protein expression of GPR54 and GnRH in GT1-7 cells. In conclusion, the Fy formula may alleviate PP via the GPR54/GnRH signaling pathway.